TRAINING TEACHERS TO USE EVIDENCE‐BASED PRACTICES FOR AUTISM: EXAMINING PROCEDURAL IMPLEMENTATION FIDELITY. Issue 2 (28th November 2014) - Stahmer, Aubyn C.; Rieth, Sarah; Lee, Ember; Reisinger, Erica M.; Mandell, David S.; Connell, James E.
<x xml:space="preserve">Abstract</x> The purpose of this study was to examine the extent to which public school teachers implemented evidence‐based interventions for students with autism in the way these practices were designed. Evidence‐based practices for students with autism are rarely incorporated into community settings, and little is known about the quality of implementation. An indicator of intervention quality is procedural implementation fidelity (the degree to which a treatment is implemented as prescribed). Procedural fidelity likely affects student outcomes. This project examined procedural implementation fidelity of three evidence‐based practices used in a randomized trial of a comprehensive program for students with autism in partnership with a large, urban school district. Results indicate that teachers in public school special education classrooms can learn to implement evidence‐based strategies; however, they require extensive training, coaching, and time to reach and maintain moderate procedural implementation fidelity. Procedural fidelity over time and across intervention strategies is examined.